Methodological recommendations for implementing an encryption algorithm using a codeword in Python - GRADINARI, Oxana; BOGDANOVA, Violeta; RUSSU, Nicolai (Acta et commentationes Științe ale Educației, 2024)
The article offers theoretical and practical material on encryption and decryption of text messages using a codeword cipher. Is shown an example of the implementation of the algorithm for cryptographic transformations of the specified cipher in the Python programming language. The development and execution of the Python program code was carried out in a free interactive cloud environment — Google Colab.